Números equilibrados aritméticos e geométricos uma abordagem na metodologia de resoluções de problemas - Santos, Bruno Costa (Universidade Federal do Tocantins, 2023)
This work aims to present some properties of the class of Arithmetic Balanced numbers and from these results extend to Geometric Balanced numbers, for that, we use notions and concepts of Combinatorial Analysis emphasizing the following contents Arrangement, Permutation, Factorial, Permutation with Repetition, Arithmetic and Geometric Means and the Inequality of Means, we intend to present general results related to the properties,